THE ANXIETY OF ROSE DA SILVA IN CHRISTOPHE GANS' SILENT HILL MOVIE (2006): A PSYCHOANALYTIC APPROACH - Iswanti, Retno Putri (2011)
The problem of the study is to reveal how major character reflects his anxiety. The objective of the study is to analyze the film based on its structural analysis and based on the psychoanalytic analysis. This study is qualitative study. The object of the study is Rose Da Silva in Silent Hill Movie. The data sources are divided into two sources namely primary data source and secondary data source. The primary data source is the film Silent Hill and the secondary data source is other sources related to the analysis such as references, author's biography, criticisms relation to the problems and material related to the study whether picking up from books or internet. The method of data collection is observation and library research. The technique of data analysis is descriptive analysis. Based on the analysis, the researcher draws two conclusions, first based on the structural analysis, Christophe Gans wants to deliver moral message that mother is God in the eyes of a child. From the structural analysis, it shows that each of the structural elements is interrelated to each other. Second, based on the psychoanalytic analysis, Christophe Gans reflects anxiety is caused by the contradiction of his id, ego and superego which cause the disharmony of hopes and fact in his life.